Board Governance Practices and Capital Structure Decisions with the Moderating Effects of Gender Diversity: Empirical Evidence from Developing Economy - Keerthana, G.; Balagobei, S. (Wayamba University, 2024)
The purpose of this study is to investigate the impact of board governance practices on capital structure decisions with the moderating effects of gender diversity. The research methodology constitutes panel regression analysis between board governance attributes and capital structure decisions; further moderation is tested with the gender diversity of listed companies in Sri Lanka from 2016 to 2020. 100 listed companies representing food, beverage and tobacco, capital goods, material and consumer services sectors in Sri Lanka were considered as a sample. This study focuses on the five aspects of board governance practices such as board size, board composition, CEO duality, board meeting and audit committee while capital structure decision is measured based on the long-term debt to total assets. The findings demonstrate that the issue of gender diversity has important implications for the capital structure decisions of the listed firms in Sri Lanka. When interacting with a high level of gender diversity, board governance characteristics are more likely to have a significant impact on firms' capital structure decisions. Board composition unveils a negative effect, and interaction between board composition and gender diversity significantly impacts firms’ leverage level. A negative effect is observed when the chief executive officer of a company also serves as the chairman of the board of directors. The effect of the audit committee turns from a positive to a negative effect when women participation on the board increases. This study offers evidence to the corporate sector about the inclusion of female representation in boardrooms, which may further increase transparency and attract capital, particularly debt. This study recommends improving monitoring processes and introducing and examining new methods that can help businesses to draw in greater resources and create an optimal capital structure. It would also assist policymakers in determining the sufficiency of available board governance reforms to improve capital structure balancing.
Keywords: Agency theory; Board composition; Board gender diversity; Capital structure decisions; CEO duality